KOMUNIKASI DAKWAH PENYULUH AGAMA ISLAM DALAM MEMBERIKAN PEMAHAMAN MODERASI BERAGAMA - Nandang Kusnandar (INSTITUT AGAMA ISLAM NEGERI METRO, 2020)
This research was conducted in Ujungberung sub-district. This research is a qualitative research that emphasizes the phenomenological aspects of Islamic religious extension agents in Ujungberung District, Bandung City. The research method in this research is descriptive qualitative. The experience of Islamic Religious Instructors in Ujungberung District in carrying out counseling on religious moderation with various joys and getting deep knowledge in the field when carrying out counseling and also there are still people who do not know about extensionists themselves. And in carrying out extension services in Ujungberung District, it is inseparable from the main duties and functions of extension workers to carry out and develop guidance activities with the function of extension personnel as informative and educational, consultative and advocacy The Islamic Religious Instructor in delivering da'wah messages through tabligh in Ujungberung District reviews several aspects including: First, in terms of the form of activities carried out by Islamic religious extension agents in Ujungberung District, in accordance with the informative and educational function of the form of extension activities carried out, consisting of Majlis Taklim, MTKD, Training, Friday Sermons and Lectures. Second, in terms of the type of message conveyed in accordance with the form of extension activities carried out. The types of messages conveyed in the activity of conveying da'wah messages through tabligh include messages of Aqidah, Morals, Fiqh, and Love for the Fatherland or in other languages ​​called Nationalism. Third, in terms of those used in conveying da'wah messages in extension activities. The media used by the extension agents consisted of print media, written media and electronic media. Ceta media consists of Al-Qur'an, Hadith books, religious books and other printed media such as leaflets or brochures.